Analysis Air Cooling Mechanism for Photovoltaic Panel by Solar Simulator - Mohd. Irwan Yusoff; Leow Wai Zhe; Muhammad Irwanto Misrun; Mohd Fareq Abd. Malek; Amelia Abdul Razak; Gomesh Nair A/L Shasidharan; Safwati Ibrahim (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Measurement the outdoor efficiency of photovoltaic (PV) panels is essential, but it is not likely an exceptional circumstance at any given moment is always repeating itself. A solar simulator was designed and fabricated for the purpose of analyzing the performance of PV panel with and without an air cooling mechanism in indoor test. Twenty units of 500 W halogen lamps with build-in reflector support by the steel structure holder act as a natural sunlight. The uniformity of the solar radiation was measured in the test area. Two units of PV panel with same characteristics were experimental in three sets of uniformity of solar radiation, which are 620, 821 and 1016 W/m². The operating temperature of PV panel with an air cooling mechanism can be decreased 2-3 ˚C compared to PV panel reference. The PV panel with an air cooling mechanism can be increased in 3-7 % of maximum power output based on solar radiation. An overall method and procedure of the measurement by the solar simulator are discussed and proposed.